STUDY OF CLIMATE CHANGE BASED ON SATELLITE IMAGERY AND GOOGLE EARTH ENGINE (IN THE CONTEXT OF THE REPUBLIC OF KARAKALPAKSTAN) - Tileubergenovich, Berdimbetov Timur; Adilbaevna, Kipshakbaeva Gauxar; ulı, Yerejepov Miyratdiyn Sharapatdiyn (Research Focus International Scientific Journal, 2026)
This study investigates the dynamics of climate change in the Republic of Karakalpakstan using multi-temporal satellite imagery and the Google Earth Engine (GEE) cloud platform. By integrating Landsat and MODIS datasets, Land Surface Temperature (LST) and the Normalized Difference Vegetation Index (NDVI) were analyzed to assess regional environmental shifts. The spatio-temporal analysis reveals a significant trend of rising surface temperatures coupled with a progressive decline in vegetation density, signaling intensified aridification and drought processes. These findings provide a robust empirical basis for environmental monitoring and the formulation of sustainable adaptation strategies in the Aral Sea region.